PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA BPR ARTHA PRIMA PERKASA - Jeany, Jeany; Siagian, Mauli Siagian (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
The research intends to show whether service quality and customer satisfaction has a positive and significant effect on customer loyalty at BPR Artha Prima Perkasa. The research sample that used was 180. The research method used in this reserach was quantitative approach and descriptive study method. The yield showed that R Square 0,384 or 38,4% of the value can be seen that service quality and customer satisfaction influence customer loyalty by 38,4% and the remaining 61,6% may affected by other factors that not tested in this research. The yield of the study based on the t test for service quality has a value of 5,179> 1,973 (ttable) and significant value of 0,000 <0,05, it can be said that variable of service quality significantly affect customer loyalty, while customer satisfaction has value of 4,461> 1,973 (ttable) and significant worth of 0,000 <0,05 can be seen that customer satisfaction has significant effect on customer loyalty. And the results of the F-test showed the value of 55,107> 3,05 (Ftable) and significant worth of 0,000 > 0,05 can be interpreted that service quality then customer satisfaction simultaneously influence customer loyalty.Keywords: Â Â Service Quality., Customer Satisfaction, Customer Loyalty